2020
DOI: 10.14233/ajchem.2020.22606
|View full text |Cite
|
Sign up to set email alerts
|

Identification of α-Glucosidase Inhibitors from Cyperus articulatus L. Rhizome Extract Using HRLC-MS/MS and Molecular Docking

Abstract: Cyperus articulatus is widely distributed in Indian subcontinent and its rhizome has been used as folk medicine in different geographical regions for treatment of diseases like malaria, epilepsy and dysentery. In present study the rhizome extracts were studied to identify the natural inhibitor compounds for α-amylase and α-glucosidase. Among six different solvent extracts of the rhizome, the acetone extract which showed to have highest phenolics and flavonoids exhibited α-glucosidase inhibition (IC50 9.1 μg/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The acetone extract of Cyperus articulatus was reported in our earlier study to have the highest phenolics (207.5μg gallic acid equivalent phenol in 1mg extract) and flavonoids (105.6μg quercetin equivalent phenol in 1mg extract) compared to other solvent extracts when extracted in different solvents of increasing polarity order. 13 Thus, the activities are in good agreement with the phytochemical composition in each extract. The oxidative damage of DNA leads to cancer initiation, and this damage is usually caused by OH radicals (which also arise due to peroxide cleavage).…”
Section: Antioxidant Properties and Application In Food And Biological Modelssupporting
confidence: 58%
See 3 more Smart Citations
“…The acetone extract of Cyperus articulatus was reported in our earlier study to have the highest phenolics (207.5μg gallic acid equivalent phenol in 1mg extract) and flavonoids (105.6μg quercetin equivalent phenol in 1mg extract) compared to other solvent extracts when extracted in different solvents of increasing polarity order. 13 Thus, the activities are in good agreement with the phytochemical composition in each extract. The oxidative damage of DNA leads to cancer initiation, and this damage is usually caused by OH radicals (which also arise due to peroxide cleavage).…”
Section: Antioxidant Properties and Application In Food And Biological Modelssupporting
confidence: 58%
“…Our earlier preliminary study on the Cyperus articulatus rhizome extract's antidiabetic property reported that acetone extract was rich in α-glucosidase inhibitors where the phenolic and non-phenolic compound fractions have shown significant inhibitory activity against the enzyme α-glucosidase. 13 This study's results, along with the reports of all the previous literature on the study of Cyperus articulatus revealed the potential pharmaceutical or medicinal values ranging from antioxidant, antibacterial, antidiabetic, anti-Alzheimer's biomolecular protection and food preservative properties. Above all, the plant is widely distributed in tropical and subtropical regions of the world, and thus the present study may be a suggestive platform for the agricultural practice of Cyperus articulatus and its effective utilization.…”
Section: Enzyme Inhibition Activity Of Rhizome Extractsmentioning
confidence: 57%
See 2 more Smart Citations
“…One of the effective ways to control diabetes is managing the excess postprandial hypoglycemia. 3 Proper diet and different classes of oral hypoglycemic drugs (such as thiazolidinediones, sulfonylureas, α-glucosidase inhibitors and biguanides) control blood glucose level (BGL). It is also reported that commercially procured drugs (such as Acarbose, Miglitol, Metformin, and Sulfonyl urea) adversely affect human health [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%